2D graphene oxide and MXene nanosheets at carbon fiber surfaces. (25th January 2023) - Adstedt, Katarina; Buxton, Madeline L.; Henderson, Luke C.; Hayne, David J.; Nepal, Dhriti; Gogotsi, Yury; Tsukruk, Vladimir V.
Abstract: Carbon fibers, which are known for their high strength to weight ratio and thermal and chemical stability, are key components in advanced structural composites. Controlling the fiber-matrix interface is key to achieving required physical performance. Functional two-dimensional (2D) materials that can conformally coat the fiber surface facilitate interface and interphase engineering for enhanced mechanical properties and added functionalities. Understanding how 2D flakes bond, integrate, and perform at carbon fiber interfaces is key to developing multifunctional high-strength composites. In this study, we focus on the surface interactions of graphene oxide (GO) and Ti3 C2 T x MXene nanoflakes at the surface of low-tension carbon fibers with and without amine functionalization by in-depth multimode scanning probe microscopy. We suggest that beyond strengthening the interfaces, GO and MXene provide efficient charge transfer with MXene also adding conductivity to the fiber surface, extending potential applications of composites to broad areas including structural supercapacitors and battery cooling/packaging materials. GO and MXene modified fibers not only create opportunities for increased interfacial adhesion in composites via increased surface roughness, but also act as anchors for bonding, energy dissipation, charge transport, and local interface stiffening. Graphical abstract: Image 1